Calculating Quality Costs in a Selected Service Enterprise - Sadkowski, Wojciech (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The article presents the calculation of quality costs, rules for its implementation and estimation, as well as an example application of this calculation in a selected service enterprise. Research Design & Methods: Empirical research on the practical application of a quality costs calculation was carried out in a service enterprise operating on the Kraków market. Findings: The implementation of a quality costs calculation in a selected service enterprise made it possible to provide information on quality costs and the relationships between groups of these costs as well as to indicate problem areas. Implications / Recommendations: Advanced service processes, high customer requirements for quality services, and fierce competition mean that the cost information provided by traditional accounting systems is insufficient for the right decisions to be made in enterprises. It is therefore necessary to implement new cost accounting systems that provide reliable information on quality-related costs. Calculating quality costs as cost accounting provides authentic information about these costs, and can be used as a tool supporting the management process. The implementation of this calculation enables enterprises to increase the efficiency of the processes, optimise costs and increase overall unit efficiency. Contribution: The results obtained should constitute the theoretical and practical basis for implementing this calculation in any service enterprise.